PERAN GURU PENGGERAK DALAM MENGIMPLEMENTASIKAN NILAI-NILAI PENGUATAN PENDIDIKAN KARAKTER DI SEKOLAH - Lorensius, Lorensius (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research examines the role of teachers as drivers in implementing character education values in schools. The character education values studied are religious, nationalist, independence, cooperation and integrity. The approach used is a descriptive qualitative approach. Data collection techniques include Focus Group Discussion (FGD), interviews, observation and documentation. This research involved 15 teachers as informants. The results of this research show that character education in schools is important for forming students' traits, attitudes, behavior, nobility of character and noble morals. Teachers have a big role in implementing values such as religion, nationalism, independence, cooperation and integrity. Implementation of these values involves the teacher's example in respecting religious differences, loving local culture, and encouraging student creativity. The teacher's role as a role model and guide is key in creating a positive school environment for the formation of student character.